Derivatisation of an Anti‐Cancer Cationic Antimicrobial Peptide and its Complexation to Platinum(II). Issue 8 (15th May 2013) - Parker, James P.; Devocelle, Marc; Marmion, Celine J.
Abstract This work focuses on the cationic antimicrobial peptide (CAP) DP18L with its known propensity to target and selectively kill cancer cells. DP18L was derivatised to dap‐DP18L where dap is 2, 3‐diaminopropionic acid. Dap facilitated binding to PtII via an (N, N') bidentate ligand to afford the first reported Pt‐CAP complex, cis‐[Pt(dap‐DP18L)Cl2)]. The syntheses of the peptides and the Pt‐peptide complex were carried out using solid phase chemistry. It was envisioned that the presence of the peptide in the complex would confer enhanced selectivity of the novel complex for neoplastic cells in addition to increasing the cellular uptake of the complex relative to cisplatin.